PENYELESAIAN SENGKETA KONSUMEN PENJAMINAN SERTIFIKAT TANAH OLEH DEVELOPER MELALUI YLPK - Habibah, Aulia Jihan Ramadhana; Tien Fitriyah, Mas Anienda (Kertha Semaya : Journal Ilmu Hukum, 2023)
Penelitian ini bertujuan untuk mengetahui bentuk kerugian yang diderita konsumen akibat perbuatan developer yang menjaminkan sertifikat tanah sebagai jaminan kredit, dan upaya hukum non-litigasi yang dapat ditempuh konsumen untuk mengembalikan haknya. Metode Hasil penelitian menunjukkan bahwa pihak konsumen menderita kerugian materiil berupa hilangnya uang pembayaran unit rumah senilai Rp. 150 juta. Jumlah tersebut telah dilunasi sejak akad jual beli, namun konsumen tidak memperoleh imbalan dari developer berupa penyerahan sertifikat tanah dan unit rumah hingga beberapa tahun setelah pelunasan. Upaya non-litigasi dapat dilakukan dengan penyelesaian sengketa secara mediasi di Kantor YLPK. Konsumen mengajukan tuntutan kepada developer untuk menyerahkan sertifikat tanah dan unit rumah. Pada prosesnya, developer tidak melakukan konfirmasi apapun dan memilih mangkir dari kedua tahap mediasi. Konsumen memutuskan untuk mempertahankan tuntutan dan melanjutkan mediasi hingga tahap akhir. The purpose of this research is to find out the form of losses suffered by consumers due to the actions of developer which guarantees land certificates as credit guarantees and non-litigation legal remedies that can be taken by consumers. The research method used is normative-empirical, which aims to ensure that the legal events that have occurred (das sein) have been carried out in accordance with the provisions of positive law in Indonesia. In this study, this method is related to the implementation of non-litigation dispute resolution contained in Law Number 8 of 1999 concerning Consumer Protection, and is associated with disputes over building use rights certificates that consumers complain about to YLPK. The results showed that the consumer suffered material losses in the form of loss of housing unit payment of Rp. 150 million. This amount has been paid since the sale and purchase agreement, but the consumer does not receive compensation from the developer in the form of handing over land certificates and housing units until several years after settlement. Non-litigation efforts can be carried out by mediating dispute resolution at the YLPK Office. Consumers filed demands for developers to hand over land certificates and housing units. In the process, the developer did not confirm anything and chose to be absent from the two mediation stages. The consumer decides to maintain the claim and continue the mediation to the final stage.